PENGEMBANGAN BUKU TEKS BAHASA INDONESIA BERBASIS DEEP LEARNING PADA MATERI TEKS DRAMA KELAS XI SMA NURUL HUDA PUCUK - Sisilia Tri Utami; Iib Marzuqi; Daniar Sofeny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning on drama text material in grade XI of SMA Nurul Huda Pucuk still faces obstacles because the teaching materials used are only Student Worksheets (LKS), so they have not been able to develop critical thinking skills, creativity, and writing and speaking skills of students optimally. This condition indicates the need to develop textbooks that are appropriate to the needs of students and the characteristics of the Independent Curriculum through a Deep Learning approach. This study aims to describe the validity, practicality, and effectiveness of Deep Learning-based Indonesian language textbooks on drama text material for grade XI of SMA Nurul Huda Pucuk. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, design experts, Indonesian language teachers, and grade XI students of SMA Nurul Huda Pucuk. Data collection techniques included observation, validation questionnaires, practicality questionnaires, and effectiveness questionnaires. Data were analyzed descriptively quantitatively using percentages to determine the level of product feasibility. The results of the study showed that the textbook obtained a validity level of 97% from material experts and 91.4% from design experts with a very valid category. Practicality based on teacher assessment reached 93% with a very practical category. Meanwhile, the effectiveness of the textbook based on student responses obtained a percentage of 91% in limited trials and 92% in field trials with a very effective category. These findings indicate that the developed textbook is suitable for use as a teaching material because it is able to support mindful, meaningful, and joyful learning, increase student engagement, and facilitate the development of writing and speaking skills in drama text material.